Metal-free difunctionalization of alkynes leading to alkenyl dithiocyanates and alkenyl diselenocyanates at room temperature - Lu, Ling-Hui; Zhou, Si-Jia; He, Wei-Bao; Xia, Wen; Chen, Ping; Yu, Xianyong; Xu, Xinhua; He, Wei-Min (Organic & biomolecular chemistry, 2018)
A simple and practical method for the synthesis of alkenyl dithiocyanates and alkenyl diselenocyanates has been developed via stereoselective difunctionalization of alkynes with NaSCN or KSeCN at room temperature. Through this methodology, a series of alkenyl dithiocyanates and alkenyl diselenocyanates could be efficiently and conveniently obtained in moderate to good yields under mild and metal-free conditions by the simple use of oxone and PhI(OAc) 2 as the oxidants.